Vertical distribution macrozoobenthos on mangrove ecosystem in coastal Ternate City - Riyadi Subur; Salim Abubakar; Marjanuddin A Sidik; Rina Rina; Sunarti Sunarti; Yuyun Abubakar; Nebuchadnezzar Akbar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Macrozoobenthos are benthic animals commonly found in substrate-based ecosystems, such as mangrove forests. Their presence in mangrove ecosystems significantly influences the decomposition activities within the substrate or sediment layers. The aim of this study was to identify species composition, species density, community structure of macrozoobenthos, and their vertical distribution within sediments on mangrove ecosystem in Ternate City. The study was conducted from August to September 2021 using the line transect method, with macrozoobenthos samples collected through iron pipe corers. Data analysis included species density, species diversity, dominance index, evenness index, niche width, microhabitat niche overlap, and the relationship between macrozoobenthos density and depth. The results showed that the macrozoobenthos species composition consisted of two species (Uca spp. and Nereis spp.), with a total of 25 individuals. Species diversity within mangrove ecosystem was found to be low, with one dominant species and a relatively even distribution. The species with the broadest habitat niche was the worm (Nereis spp.), while significant microhabitat niche overlap occurred between the worm (Nereis spp.) and the crab (Uca spp.). Simple linear regression analysis indicated that substrate depth did not correlate with macrozoobenthos species density.Keywords:aquaticbenthoscoastalfaunaterrestrial